Cryptococcosis complicating diabetes mellitus: a scoping review - Nsenga, Lauryn; Kajjimu, Jonathan; Olum, Ronald; Ninsiima, Sandra; Kyazze, Andrew Peter; Ssekamatte, Phillip; Kibirige, Davis; Baruch Baluku, Joseph; Andia-Biraro, Irene; Bongomin, Felix (Therapeutic advances in infectious disease, 2021)
A better understanding of the epidemiology of cryptococcal infection in HIVnegative individuals is an international research interest. Immune dysfunction in diabetes mellitus (DM) significantly increases the risk of acquiring and reactivation of infection due to Cryptococcus neoformans. Risk factors and outcomes of cryptococcosis in DM are not well documented. Objective: The objective of this study was to determine the clinical characteristics and outcomes of cryptococcal infections in persons living with DM. Methods: MEDLINE (via PubMed), EMBASE, and the Cochrane Library databases were searched in November 2020. The searches covered the period between 1980 and 2020.We included studies that reported confirmed cryptococcosis in patients with DM. Reference lists of included articles were also searched, and additional studies were included if appropriate. No language restriction was applied. Single case reports, case series and original articles were included whereas review articles were excluded. Results: A total of 28 studies (24 single case reports, 4 retrospectives) were included involving 47 unique patients from Asia (17 cases), North America (six cases), South America (three cases) and Africa (two cases). Men constituted 75% (n = 18) of the cases. Median age was 60.5 (range: 27–79) years. The majority of the patients had cryptococcal meningitis (68.1%, n = 32) followed by disseminated cryptococcosis (6.4%, n = 7), and others (isolated cutaneous disease one, peritonitis one, pleural one, thyroid one, adrenal one). Diagnosis was achieved through either culture and microscopy (38/47), cryptococcal antigen tests (9/47) or histopathology (9/47) singly or in a combination. All-cause mortality was 38.3% (n = 18). Among those with meningitis mortality was 36.2%. Conclusion: A wide spectrum of cryptococcal infections with varying severity occurs in DM. Mortality remains unacceptably high. There is a need for more studies to characterize better cryptococcal disease in DM.
Keywords: Clinical characteristics; Cryptococcosis; Diabetes mellitus; Mortality